Research on the Application of Computer In Real Estate Engineering Audit. Issue 3 (August 2021) - Su, Di; Chen, Huihua
Abstract: The real estate audit work is an important link to promote the real estate project. However, there are many problems to be solved in the process of real estate project audit. For example, the main existing problems involve many examination and approval departments, complex examination and approval process and uncertain examination and approval boundaries. Based on this, this paper first studies the problems and countermeasures in the approval of real estate construction projects, and the practical application of computer in the audit of real estate projects to discuss for the reader's reference.